Phosphate-induced autophagy counteracts vascular calcification by reducing matrix vesicle release - Dai, Xiao-Yan; Zhao, Ming-Ming; Cai, Yan; Guan, Qing-Cong; Zhao, Ying; Guan, Youfei; Kong, Wei; Zhu, Wei-Guo; Xu, Ming-Jiang; Wang, Xian (Kidney international, 2013)
Autophagy is a dynamic and highly regulated process of self-digestion responsible for cell survival and reaction to oxidative stress. As oxidative stress is increased in uremia and is associated with vascular calcification, we studied the role of autophagy in vascular calcification induced by phosphate. In an in vitro phosphate-induced calcification model of vascular smooth muscle cells (VSMCs) and in an in vivo model of chronic renal failure, autophagy was inhibited by the superoxide dismutase mimic MnTMPyP, superoxide dismutase-2 overexpression, and by knockdown of the sodium-dependent phosphate cotransporter Pit1. Although phosphate-induced VSMC apoptosis was reduced by an inhibitor of autophagy (3-methyladenine) and knockdown of autophagy protein 5, calcium deposition in VSMCs was increased during inhibition of autophagy, even with the apoptosis inhibitor Z-VAD-FMK. An inducer of autophagy, valproic acid, decreased calcification. Furthermore, 3-methyladenine significantly promoted phosphate-induced matrix vesicle release with increased alkaline phosphatase activity. Thus, autophagy may be an endogenous protective mechanism counteracting phosphate-induced vascular calcification by reducing matrix vesicle release. Therapeutic agents influencing the autophagic response may be of benefit to treat aging or disease-related vascular calcification and osteoporosis.